2020
DOI: 10.18231/2394-4994.2018.0115
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled double blind study comparing the efficacy of epidural ropivacaine and bupivacaine with fentanyl for labor analgesia

Abstract: Introduction and Aim: Ropivacaine and bupivacaine have been found to provide adequate labor analgesia when given epidurally. The aim of this randomized double blind study was to compare the onset of sensory block in epidural ropivacaine and bupivacaine with Fentanyl for labor analgesia and to assess the maternal and fetal outcome. Materials and Methods: In this prospective double blind study, 60 ASA II parturients with singleton vertex presentation were randomly allocated to two groups of 30 each. Group R rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sufentanil has stronger analgesic effect and longer action time, so sufentanil has unique advantages in epidural labor analgesia. During intrathecal administration of sufentanil, it mainly acts on the opioid receptors on the surface of the spinal cord, and its analgesic effect is about 4/5 times higher compared to fentanyl [ 40 ]. The high placental transfer rate of sufentanil has raised concerns about the safety of sufentanil, but it has been reported that sufentanil is absorbed into the epidural space very little, so it has little effect on the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil has stronger analgesic effect and longer action time, so sufentanil has unique advantages in epidural labor analgesia. During intrathecal administration of sufentanil, it mainly acts on the opioid receptors on the surface of the spinal cord, and its analgesic effect is about 4/5 times higher compared to fentanyl [ 40 ]. The high placental transfer rate of sufentanil has raised concerns about the safety of sufentanil, but it has been reported that sufentanil is absorbed into the epidural space very little, so it has little effect on the fetus.…”
Section: Discussionmentioning
confidence: 99%